2018
DOI: 10.1016/s2352-3018(18)30062-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-disclosed men who have sex with men in UK HIV transmission networks: phylogenetic analysis of surveillance data

Abstract: National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Older people were more likely to be infected through heterosexual contact (113/126, 89.68%), in contrast, the proportion of MSM (117/207, 56.52%) was higher than whom infected through heterosexual contact (89/207, 43.00%) in non-old aged group. Although there is the possibility of misclassification of MSM as heterosexuals and it has been confirmed in investigations conducted in UK, [25, 26] older people influenced by Chinese traditional culture especially in underdeveloped areas of China are more likely to be heterosexual, and it is also found that some of them are even involved in drug-used heterosexual activities [27].…”
Section: Resultsmentioning
confidence: 99%
“…Older people were more likely to be infected through heterosexual contact (113/126, 89.68%), in contrast, the proportion of MSM (117/207, 56.52%) was higher than whom infected through heterosexual contact (89/207, 43.00%) in non-old aged group. Although there is the possibility of misclassification of MSM as heterosexuals and it has been confirmed in investigations conducted in UK, [25, 26] older people influenced by Chinese traditional culture especially in underdeveloped areas of China are more likely to be heterosexual, and it is also found that some of them are even involved in drug-used heterosexual activities [27].…”
Section: Resultsmentioning
confidence: 99%
“…For example, having met a sexual partner online was identified by random forest analysis to be the strongest discriminator of small and large clusters. The random forest analysis indicates that those participants found among the largest clusters were Black men who reported meeting partners online but reported no risk factors, suggesting the important role of non-disclosure of MSM as a risk factor for HIV infection [29]. The discrepancy between the numbers of named and claimed high-risk partners, taken to be the number of anonymous partners herein, was also associated with large clusters.…”
Section: Discussionmentioning
confidence: 89%
“…Most of the articles focused on this issue stress that, until solved, the problem of MSM non-disclosure for various reasons constitutes a blind spot in HIV epidemiology (Hué et al, 2014;Ragonnet-Cronin et al, 2018). The articles also often highlight that non-disclosed MSM must be uncovered because they are a potential bridge between MSM HIV and heterosexual HIV dynamics (Ragonnet-Cronin et al, 2019).…”
Section: Content Analysis Andmentioning
confidence: 99%